2009
DOI: 10.17305/bjbms.2009.2858
|View full text |Cite
|
Sign up to set email alerts
|

Laser Therapy of Painful Shoulder and Shoulder-Hand Syndrome in Treatment of Patients after the Stroke

Abstract: The common complication after stroke is pain and dysfunction of shoulder of paralyzed arm, as well as the swelling of the hand. The aim of this study was to determine the effects of LASER therapy and to correlate with electrotherapy (TENS, stabile galvanization) in subjects after stroke. We analyzed 70 subjects after stroke with pain in shoulder and oedema of paralyzed hand. The examinees were divided in two groups of 35, and they were treated in the Clinic for Physical Medicine and Rehabilitation in Tuzla dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 7 publications
1
14
0
16
Order By: Relevance
“…29,37,38 High-intensity laser therapy could control inflammation by reducing C-reactive protein, neopterin, interleukin 1, and prostaglandin levels. 38 The current study results were in agreement with other studies [39][40][41] which revealed that laser therapy has anti-edema effect. Also, laser led to reduction of pain, swelling, disability and improvement of independency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…29,37,38 High-intensity laser therapy could control inflammation by reducing C-reactive protein, neopterin, interleukin 1, and prostaglandin levels. 38 The current study results were in agreement with other studies [39][40][41] which revealed that laser therapy has anti-edema effect. Also, laser led to reduction of pain, swelling, disability and improvement of independency.…”
Section: Discussionsupporting
confidence: 92%
“…Also, laser led to reduction of pain, swelling, disability and improvement of independency. 41 In this study, the exercise program in the control group also increased the handgrip strength, decreased the swelling joints counts, tenderness joints counts and pain. The results of the current studies were in agreement with other studies that reported significant improvement in handgrip strength, pinch strength, dexterity and quality of life, and a significant decrease of pain in the exercise group.…”
Section: Discussionmentioning
confidence: 49%
“…Also, significantly higher pain and edema reduction was achieved by the application of LLLT in patients with shoulderhand syndrome after cerebral ischemia, compared to the group in which electrotherapy (TENS, stabile galvanization) was applied (33).…”
mentioning
confidence: 89%
“…58 Despite their common presence, clinical trials investigated treatment options(benzodiazepines, botulinum toxin or baclofen) are all non comparative, so their effectiveness is yet to be established. 59,60 Regarding physical modalities in treatment of CRPS, there are limited evidences of superior effect of low level laser therapy to interferential currents in decreasing temperature in extremity 61 , pain, swelling and disability compared with electrotherapy (TENS and stabile galvanization) 62 Electromagnetic field therapy has been shown ineffective for CRPS in the high quality RCT. 63 Interestingly, there are no studies on transcutaneous electrical nerve stimulation(TENS) although it is an physical modality widely used for pain control, compering effects of physical and occupational therapy for CRPS, it is shown that both have positive effect on pain reduction and improved function, with some of the studies showing a slightly better effect and cost effectiveness for physical therapy 64,65 .…”
Section: Physical Therapymentioning
confidence: 99%